PENERAPAN METODE SAS (STRUKTUR ANALITIK SINTETIK) DALAM MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN DI KELAS I SDN 009 KERAMPAL KECAMATAN BATANG GANSAL - Eva Renlia; Otang Kurniaman; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The process of learning the Indonesian language in the class I SDN 009 Kerampal Kecamatan Batang Gansal on average are still difficulties in reading in textbooks and written Indonesian teacher at the blackboard. The low reading skills seen among the 24 first-class students only 5 students (20.8%) were able to read fluently and correctly, while 19 students (79.2%) have not been able to read fluently and correctly. The low reading skills of students in class I in the Indonesian language teaching occurs due to several factors in learning, among others: (a) students lack of concentration in reading; (b) students are less familiar with letters; (c) teachers do not give students the opportunity to read; (d) teachers do not use media that can attract students' interest in reading; and (e) teachers are not using the learning model that accelerates students' skills in reading. With symptoms that are encountered in SDN 009 Kerampal Kecamatan Batang Gansal, the writer wants to hold a classroom action research learning model SAS (struktual Analytical Synthetic). Application of SAS method can improve learning outcomes Early reading skills of students in class I SDN 009 Kerampal Kecamatan Batang Gansal in which the average value of 58.96 class on preliminary data, an increase in the daily tests first cycle to 62.67, then increased in cycle II to 70. SAS methods can help classical completeness where students who pass the preliminary data as much as five students (20.8%), the first cycle to 14 students (58.3%) and the second cycle to 21 students (87.5%). SAS Learning method can increase the activity of students in the first cycle in which the first meeting of student activity 40%, the second meeting of the student activity 50%. The third meeting of the second cycle of student activity 60%, At the fourth meeting of the second cycle increased to 75%. Then contextual learning can enhance the activity of teachers in the first cycle in which the first meeting of teacher activity 45%, the second meeting of the activities of teachers 60%. The third meeting of the second cycle of teacher activity 70%, At the fourth meeting of the second cycle of teacher activity increased to 75%Keywords: SAS Method (Analytical struktual Synthetic), reading skills